2015
DOI: 10.5812/jjm.20980v2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clonal Dissemination of Metallo-Beta-Lactamase-Producing Pseudomonas aeruginosa in Kermanshah

Abstract: Background:Pseudomonas aeruginosa is an opportunistic pathogen associated with nosocomial infections. The emergence and dissemination of metallo-beta-lactamases (MBLs) has contributed to the high rate of resistance among P. aeruginosa isolates.Objectives:The purpose of this study was to describe the prevalence and the clonal dissemination of MBL- producing P. aeruginosa isolates collected from major hospitals in Kermanshah.Materials and Methods:Antibiotic susceptibility testing was performed using the minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
2
15
1
1
Order By: Relevance
“…In our finding, 37.5% MBL production by P. aeruginosa was observed. A study conducted in India, Brazil and Iran revealed 32.9%, 30%, 48.3% MBL production respectively [ 48 – 50 ]; however those studies used clinical specimen. These P. aeruginosa isolates could be causes for several nosocomial infections, illustrating the need for proper infection control practices [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our finding, 37.5% MBL production by P. aeruginosa was observed. A study conducted in India, Brazil and Iran revealed 32.9%, 30%, 48.3% MBL production respectively [ 48 – 50 ]; however those studies used clinical specimen. These P. aeruginosa isolates could be causes for several nosocomial infections, illustrating the need for proper infection control practices [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the multi-drug resistance, special attention was given in this study to P . aeruginosa resistant to carbapenems, considering the significant increase of this resistance in Latin America and widespread of different clones associated with the production enzymes of the MBL type [ 55 58 ]. The predominant MBL-encoding gene in Brazil is bla SPM-1 , which has been disseminated by the MDR P .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that infections caused by drug-resistant strains of P. aeruginosa are associated with significant increases in mortality, morbidity, lengths of hospital stay or chronic care, need for surgical interventions, and overall costs of treating the infection (21). The emergence of PDR strains of P. aeruginosa , which are resistant to all current antibiotics, has led to concerted efforts to find alternative approaches to treatment, including older antibiotics that may have activity against these strains (22-25). In light of the increased antibiotic resistance of MDR microorganisms for which no adequate therapeutic options exist, a joint initiative by the ECDC and the CDC recently created standardized international definitions for MDR, XDR, and PDR in some bacteria.…”
Section: Discussionmentioning
confidence: 99%